Implementation of the Muhadharah Program in Developing Students Da'wah Skills at MTs Al-Ittihadiyah Bromo - Nadia Adiningrat; Hasan Asari (Vifada Journal of Education, 2026)
This study aims to determine the implementation of the muhadharah program in developing students' da'wah skills at MTs Al-Ittihadiyah Bromo The focus of the study includes the planning, implementation, and evaluation of the muhadharah program in developing students' da'wah skills. The method used in this study is qualitative with data collection techniques through interviews, observation, and documentation. Data analysis is carried out through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of the muhadharah program is effective in developing students' da'wah skills. The da'wah skills in question include the courage to appear in public, proficiency in delivering da'wah in three languages, fluency in reading the holy verses of the Qur'an, and being accustomed to being a prayer reader. Although there are obstacles such as inadequate available facilities and infrastructure, low levels of student participation that tend to be dominated by the same person, and lack of teacher creativity in the coaching process. Therefore, continuous improvement efforts are needed so that the muhadharah program is implemented optimally in developing students' da'wah skills.